Social-emotional competence in early adolescence: the role of prosocial behaviour and peer acceptance - Purna, Rozi Sastra; Sari, Liliyana; Angraini, Fitri; Afrilda, Fauziah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In addition to academic achievement, social-emotional competence has been increasingly considered a fundamental predictor of success in various aspects of life, particularly in adolescents. However, social-emotional competence among adolescents is currently in declining trend. The current research aimed to investigate psychological factors influencing early adolescents' social-emotional competence. This research employed quantitative methods. After filling in informed consent, 380 junior high school students aged 12 and 14 years in Padang city, Indonesia was recruited through the cluster sampling technique. All participants completed three validated questionnaires, such as the Social and Emotional Competency Questionnaire, Prosocial Tendencies Measure, and Peer Acceptance Scale. Structural equation modelling (SEM) analysis showed that prosocial behaviour and peer acceptance had a significant influence on social-emotional competence among early adolescents. Further analysis also revealed that peer acceptance partially mediated the relationships between prosocial behaviour and social-emotional competence. Overall, this research model contributed 39.6% to explain the relationship between the studied variables. Therefore, these findings suggest that encouraging prosocial behaviours and being acknowledged by peers are established as two essential factors in promoting social-emotional competence among early adolescents.